2019
DOI: 10.2217/cer-2018-0124
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness of elagolix versus leuprolide acetate for treating moderate-to-severe endometriosis pain in the USA

Abstract: Aim: To assess the cost–effectiveness of elagolix versus leuprolide acetate in women with moderate to severe endometriosis pain. Methods: A Markov model was developed. The efficacy of leuprolide acetate was derived from statistical prediction models using elagolix trial data. Model inputs were extracted from Phase III clinical trials and published literature. Results: Compared with leuprolide acetate, elagolix generated positive net monetary benefit (NMB) assuming a payer's willingness-to-pay threshold of US$1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In their 2018 assessment of elagolix, the Institute for Clinical and Economic Review (ICER) reported that ''use of elagolix to treat moderate-to-severe endometriosis-related pain provides clinical benefit in terms of gains in healthrelated quality of life relative to no active treatment.'' 53 In 2019, Wang et al 54 published a cost-effectiveness evaluation that indirectly compared elagolix with leuprolide acetate, described as one of the most commonly used second-line therapies for endometriosis. Both elagolix treatment regimens analyzed (150 mg once daily for 24 months and 200 mg twice daily for 6 months) were found to be more costeffective than leuprolide acetate (11.25 mg every 3 months for 12 months, with add-back norethindrone acetate during the latter 6 months).…”
Section: Managing Endometriosis As a Chronic Disease: Long-term Treatmentioning
confidence: 99%
“…In their 2018 assessment of elagolix, the Institute for Clinical and Economic Review (ICER) reported that ''use of elagolix to treat moderate-to-severe endometriosis-related pain provides clinical benefit in terms of gains in healthrelated quality of life relative to no active treatment.'' 53 In 2019, Wang et al 54 published a cost-effectiveness evaluation that indirectly compared elagolix with leuprolide acetate, described as one of the most commonly used second-line therapies for endometriosis. Both elagolix treatment regimens analyzed (150 mg once daily for 24 months and 200 mg twice daily for 6 months) were found to be more costeffective than leuprolide acetate (11.25 mg every 3 months for 12 months, with add-back norethindrone acetate during the latter 6 months).…”
Section: Managing Endometriosis As a Chronic Disease: Long-term Treatmentioning
confidence: 99%
“…Over 2 years, both doses were also associated with a positive NMB relative to leuprolide acetate (US$2374 and US$1342, respectively). 44 The results were robust to sensitivity analyses. 42 Mean hours gained in household productivity, defined as −1 × LS mean change from baseline in hours of household productivity lost due to absenteeism, presenteeism and total hours lost (absenteeism + presenteeism).…”
Section: Effect Of Elagolix On Non-pain Outcomesmentioning
confidence: 90%
“…Over 2 years, both doses were also associated with a positive NMB relative to leuprolide acetate (US$2374 and US$1342, respectively). 44 The results were robust to sensitivity analyses.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another US study, and the third most read article of 2019, comes from Wang et al, who assessed the costeffectiveness of elagolix versus leuprolide acetate in women with moderate-to-severe endometriosis pain; a condition that has been estimated to affect between 4 and 10% of women in their reproductive years [9].…”
Section: Content Highlights Of 2019mentioning
confidence: 99%